2020
DOI: 10.1111/plb.13194
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth shapes the effects of elevation on the content and variability of flavonoids in subalpine bilberry stands

Abstract: The study of morphological and physiological responses of shrubs to climate is crucial for the understanding of future scenarios regarding climate change. In this light, studying shrub growth and physiological acclimation along an elevation gradient might be insightful. The phenolic metabolic pathway represents a powerful tool to interpret such processes. In the South‐Eastern Alps, we investigated the relationships between elevation, plant traits (i.e. age, xylem ring width, annual shoot length), plant–plant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…On the other hand, the trend of increasing total flavonoid content in southern latitudes can be explain by increased UV-B radiation at higher elevations compared with northern, suggesting a greater contribution of flavonoids to radical scavenging potential. In this regard, our findings are partially explained by previous studies showing the promotion of flavonoid synthesis at a high altitude due to increased UV-B radiation and oxidative stress [ 37 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…On the other hand, the trend of increasing total flavonoid content in southern latitudes can be explain by increased UV-B radiation at higher elevations compared with northern, suggesting a greater contribution of flavonoids to radical scavenging potential. In this regard, our findings are partially explained by previous studies showing the promotion of flavonoid synthesis at a high altitude due to increased UV-B radiation and oxidative stress [ 37 ].…”
Section: Discussionsupporting
confidence: 67%
“…However, previous studies on different plant species have shown the variable effects of environmental gradients on phenolic metabolic pathways [ 34 , 35 ]. The opposite trend of accumulation of phenolic compounds, depending on the elevation, was found in Vaccinium myrtillus L. both for groups of compounds and for part of plants [ 36 , 37 ]. Nataraj et al [ 38 ] reported that the concentration of phenolic compounds decreased in the leaves of Artemisia brevifolia Wall ex DC.…”
Section: Discussionmentioning
confidence: 99%
“…Plants often employ mixed anti‐herbivore defense strategies that involve production of various types of secondary metabolites, which vary in their effectiveness against different herbivores but also play a huge role in plant adaptation to adverse environmental conditions (Filippi et al, 2021; Lankau, 2007; War et al, 2012). Carbon‐based metabolites such as tannins and flavonoids (phenolic compounds) are well‐known to act as anti‐herbivore defenses by affecting the feeding behavior and development of insect herbivores (Müller‐Schärer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…So far, investigations targeting snow cover effects mainly explore single plant’s parameters as radial annual growth or shoot elongation ( Rixen et al, 2010 ; Schmidt et al, 2010 ; Pellizzari et al, 2014 ; Francon et al, 2017 ; Carrer et al, 2019 ), while other key functional traits or physiological parameters crucial for plant fitness, productivity, and survival, as leaf traits or non-structural carbohydrate content, are mostly neglected, especially in shrub-related studies ( Wipf et al, 2009 ; Sedlacek et al, 2015 ; Filippi et al, 2021 ). In fact, leaves and stomata features, driving photosynthesis and transpiration processes, reflect plant functioning in specific growing conditions ( Chapin et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%